Mathematical modeling of torsional surface wave propagation in a non-homogeneous transverse isotropic elastic solid semi-infinite medium under a layer - Sethi, Madhu; Sharma, Anupam Deep; Vasishth, A. (Zielona Góra: Uniwersytet Zielonogórski)
The present paper deals with the mathematical modeling of the propagation of torsional surface waves in a non-homogeneous transverse isotropic elastic half-space under a rigid layer. Both rigidities and density of the half-space are assumed to vary inversely linearly with depth. Separation of variable method has been used to get the analytical solutions for the dispersion equation of the torsional surface waves. Also, the effects of non-homogeneities on the phase velocity of torsional surface waves have been shown graphically. Also, dispersion equations have been derived for some particular cases, which are in complete agreement with some classical results.
Keywords: non-homogeneous media; torsional surface waves; rigidity